Development of e-commerce quality and evaluation framework based on technical and user perspectives - Abd Wahab, Alawiyah; Yahaya, Jamaiah; Baharom, Fauziah; Tarawneh, Omar (2010)
This research aims to construct a quality framework for effective website applications specifically for B-to-C e-commerce application that hopefully can guarantee the development of quality software in the organisations in this industry.Finding from previous studies indicate that this problem occurs because of ignorance of consumer needs in their websites development.The proposed framework consists of two main attributes of quality: the behavioural and the user aspect.The behavioural attributes deals with assessing e-commerce in technical aspects to ensure the quality of the software.While the user aspect deal with user expectation and satisfaction toward quality e-commerce application.These two components of quality produce a balance model between technical requirement and human factor.The objectives of this research are to investigate and identify e-commerce evaluation attributes based on user’s perspective, to identify evaluation attributes based on e-commerce application behaviour (technical) perspective, to design an architecture of attribute’s measures and metrics and to construct a new integrated e-commerce evaluation framework based on users and technical perspectives.The research will be conducted in four main phases which include: 1) the theoretical and empirical study; 2) design the architecture of attributes, measures and metrics; 3) construction of an integrated e-commerce quality evaluation framework, and 4) confirmation study.The framework will provide a complete mechanism for assessing e-commerce B-2-C application.This research will offer missing factors for e-commerce assessment from consumer perspectives (consumer aspect) that can be used to improve organization websites to meet the consumers need and to keep the organization competitive and sustainable.